2022
DOI: 10.1039/d2bm00022a
|View full text |Cite
|
Sign up to set email alerts
|

Development of gelatin methacrylate (GelMa) hydrogels for versatile intracavitary applications

Abstract: Applicability of hydrogels as drug delivery systems is on the rise due to their highly tunable degree of polymeric crosslinking to attain varying rates of payload release. Sustaining the release...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…The methylene peak of lysine is at 2.9 ppm, and then, the substitution rate is calculated based on 7.2 ppm phenylalanine. These results indicate that gelatin can be modified with methacryloyl substitutes at specific amino acid residues, allowing for the formation of covalent crosslinks with the photoinitiator . The degree of modification is quantified as the substitution rate, which represents the percentage of amino acids in gelatin that have been successfully replaced with methacryloyl groups.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The methylene peak of lysine is at 2.9 ppm, and then, the substitution rate is calculated based on 7.2 ppm phenylalanine. These results indicate that gelatin can be modified with methacryloyl substitutes at specific amino acid residues, allowing for the formation of covalent crosslinks with the photoinitiator . The degree of modification is quantified as the substitution rate, which represents the percentage of amino acids in gelatin that have been successfully replaced with methacryloyl groups.…”
Section: Resultsmentioning
confidence: 95%
“…These results indicate that gelatin can be modified with methacryloyl substitutes at specific amino acid residues, allowing for the formation of covalent crosslinks with the photoinitiator. 27 The degree of modification is quantified as the substitution rate, which represents the percentage of amino acids in gelatin that have been successfully replaced with methacryloyl groups. The substitution rate is a crucial parameter as it directly influences the properties of GelMA, including its mechanical characteristics, 28 swelling behavior, and pore formation.…”
Section: Materials Characterizationmentioning
confidence: 99%
“…They found that the cells remained viable after contact with the tested material. Kulkarni et al tested the biocompatibility of a GelMA hydrogel through an MTT assay, and the cell viability found was above 80% [ 34 , 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…The cells were then treated with the plain drug and the prepared nanoemulsion at a concentration ranging from 0.09 to 12.5 µM along with the no treatment media as control, followed by incubation over a period of 72 h at 37 °C/5% CO 2 . The cellular viability was then evaluated using an MTT assay using a Tecan Spark 10M Plate reader (Tecan, Männedorf, Switzerland), following protocols established earlier by our group [ 36 ]. All cytotoxicity studies were repeated at least three times with n = 6 each time.…”
Section: Methodsmentioning
confidence: 99%